Administrative fines and liquidated damages In transport infrastructure concessions - Manayalle Chirinos, Alejandro (2016)
Concession agreements in infrastructure have civil and administrative nature making possible for the Government to apply administrative fines and liquidated damages provisions in case of concessionaires breach.On the transportation infrastructure side, the authors explain that theoretical and practical misunderstandings are present between both legal systems and suggest amendments to the legal framework to overcome such problems.The analysis of these issues is supported on the review of several concession agreements and a comparison with the regulation of the matter in other markets.